KEPEMILIKAN HAK ATAS TANAH YANG TIDAK TERCATAT DI BUKU C KELURAHAN - Fatin Hamamah; Mohammad Saleh (Jurnal HUKUM BISNIS, 2023)
Based on the results of the discussion, it was found that the Letter C Book, as initial evidence in accordance with Articles 1866 of the Civil Code and 164 HIR, to obtain a land right in carrying out land registration where these lands are lands that are subject to customary law. With regard to Letter C quotations, many people still hold that they do not understand that Letter C quotations, or the mention Girik by the public, are actually only a basis for tax collection. Owners of proof of letter C often consider that girik as proof of ownership of land. Excerpts of Letter C are in practice kept by the Lurah/Village Head, who already has strong evidence, while Citations of Kelurahan Letters are the results of detailed data collection in 1950 before the enactment of the Basic Agrarian Law. With the enactment of Government Regulation Number 24 of 1997 concerning Land Registration, the Subdistrict Letter C quotation is proof of tax payment and can be applied for as the acquisition of land rights. For this reason, with the evidence of Letter C book citations, the land registration system used is usually used to obtain land title certificates for the first time, meaning that previously these lands had not been certified.